(untitled) (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2022)
With the emergence of new time requirements for the quality of educational services, which is affected by management in functioning business processes, the available research in the field of resource allocation in the management of complex processes was studied. An overview of the basic concepts is made, a classification of resource allocation tasks and methods of their solution is given. According to the publications, it can be said that for a long time the issues of management in organizations based on the effective allocation of resources remain relevant. Many approaches and methods have been used to solve problems in this area. This article analyzes published articles on problematic issues of resource allocation in organizations. The formulation of the task of managing the allocation of resources in the organization of the educational process is defined, which requires the development of new approaches and methods – planning the optimal teaching load of the teacher under given constraints